Pembrolizumab or placebo with chemoradiotherapy followed by pembrolizumab or placebo for newly diagnosed, high-risk, locally advanced cervical cancer (ENGOT-cx11/GOG-3047/KEYNOTE-A18): overall survival results from a randomised, double-blind, placebo-controlled, phase 3 trial - Lorusso, Domenica; Xiang, Yang; Hasegawa, Kosei; Scambia, Giovanni; Leiva, Manuel; Ramos-Elias, Pier; Acevedo, Alejandro; Cvek, Jakub; Randall, Leslie; Pereira de Santana Gomes, Andrea Juliana; Contreras Mejía, Fernando; Helpman, Limor; et al. (Lancet, 2024)
BACKGROUND: At the first interim analysis of the phase 3 ENGOT-cx11/GOG-3047/KEYNOTE-A18 study, the addition of pembrolizumab to chemoradiotherapy provided a statistically significant and clinically meaningful improvement in progression-free survival in patients with locally advanced cervical cancer. We report the overall survival results from the second interim analysis of this study. METHODS: Eligible patients with newly diagnosed, high-risk (FIGO 2014 stage IB2-IIB with node-positive disease or stage III-IVA regardless of nodal status), locally advanced, histologically confirmed, squamous cell carcinoma, adenocarcinoma, or adenosquamous cervical cancer were randomly assigned 1:1 to receive five cycles of pembrolizumab (200 mg) or placebo every 3 weeks with concurrent chemoradiotherapy, followed by 15 cycles of pembrolizumab (400 mg) or placebo every 6 weeks. Pembrolizumab or placebo and cisplatin were administered intravenously. Patients were stratified at randomisation by planned external beam radiotherapy type (intensity-modulated radiotherapy [IMRT] or volumetric-modulated arc therapy [VMAT] vs non-IMRT or non-VMAT), cervical cancer stage at screening (FIGO 2014 stage IB2-IIB node positive vs III-IVA), and planned total radiotherapy (external beam radiotherapy plus brachytherapy) dose (<70 Gy vs ≥70 Gy [equivalent dose of 2 Gy]). Primary endpoints were progression-free survival per RECIST 1.1 by investigator or by histopathological confirmation of suspected disease progression and overall survival defined as the time from randomisation to death due to any cause. Safety was a secondary endpoint. FINDINGS: Between June 9, 2020, and Dec 15, 2022, 1060 patients at 176 sites in 30 countries across Asia, Australia, Europe, North America, and South America were randomly assigned to treatment, with 529 patients in the pembrolizumab-chemoradiotherapy group and 531 patients in the placebo-chemoradiotherapy group. At the protocol-specified second interim analysis (data cutoff Jan 8, 2024), median follow-up was 29·9 months (IQR 23·3-34·3). Median overall survival was not reached in either group; 36-month overall survival was 82·6% (95% CI 78·4-86·1) in the pembrolizumab-chemoradiotherapy group and 74·8% (70·1-78·8) in the placebo-chemoradiotherapy group. The hazard ratio for death was 0·67 (95% CI 0·50-0·90; p=0·0040), meeting the protocol-specified primary objective. 413 (78%) of 528 patients in the pembrolizumab-chemoradiotherapy group and 371 (70%) of 530 in the placebo-chemoradiotherapy group had a grade 3 or higher adverse event, with anaemia, white blood cell count decreased, and neutrophil count decreased being the most common adverse events. Potentially immune-mediated adverse events occurred in 206 (39%) of 528 patients in the pembrolizumab-chemoradiotherapy group and 90 (17%) of 530 patients in the placebo-chemoradiotherapy group. This study is registered with ClinicalTrials.gov, NCT04221945. INTERPRETATION: Pembrolizumab plus chemoradiotherapy significantly improved overall survival in patients with locally advanced cervical cancer These data, together with results from the first interim analysis, support this immuno-chemoradiotherapy strategy as a new standard of care for this population. FUNDING: Merck Sharp & Dohme, a subsidiary of Merck & Co.
Keywords: adenoskvamózní karcinom; Adenocarcinoma; chemoradioterapie; Humans; Antineoplastic Agents, Immunological; lidé středního věku; Double-Blind Method; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; nádory děložního čípku; senioři; lidé; humanizované monoklonální protilátky; dvojitá slepá metoda; Carcinoma, Adenosquamous; doba přežití bez progrese choroby; Adult; Antibodies, Monoclonal, Humanized; staging nádorů; ženské pohlaví; Middle Aged; Antineoplastic Combined Chemotherapy Protocols; Uterine Cervical Neoplasms; protinádorové látky imunologicky aktivní; Progression-Free Survival; adenokarcinom; spinocelulární karcinom; Carcinoma, Squamous Cell; Neoplasm Staging; Chemoradiotherapy